2019
DOI: 10.1111/jgh.14816
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pretreatment tumor growth rate on objective response of hepatocellular carcinoma treated with transarterial chemoembolization

Abstract: Background and Aim The study aims to assess the influence of pretreatment tumor growth rate (TGR) on modified response evaluation criteria in solid tumors (mRECIST) objective response (OR) after a first session of selective transarterial chemoembolization (TACE) for the treatment of hepatocellular carcinoma (HCC). Methods One hundred fifteen patients (101 men [88%], mean 65.1 ± 10.5 years [range 26–87]) with 169 tumors (mean 34.2 ± 29.3 mm [10–160]), undergoing a first session of selective TACE for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
3
11
1
Order By: Relevance
“…Nevertheless, we also found that high TGR 0 was correlated with low DCB rate and a tendency towards lower ORR. Similar to our observation, Yvonne Purcell et al elucidated that the mean pre-treatment TGR was not significant different between the objective response (OR) and non-OR group in hepatocellular carcinoma treated with transarterial chemoembolization (19). This is clinically relevant because it has been showed that ORR was poorly correlated with long-term survival for immunotherapy (12,31), indicating the inadequacy of RECIST criteria which only capture tumor volume change but miss out temporal information.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, we also found that high TGR 0 was correlated with low DCB rate and a tendency towards lower ORR. Similar to our observation, Yvonne Purcell et al elucidated that the mean pre-treatment TGR was not significant different between the objective response (OR) and non-OR group in hepatocellular carcinoma treated with transarterial chemoembolization (19). This is clinically relevant because it has been showed that ORR was poorly correlated with long-term survival for immunotherapy (12,31), indicating the inadequacy of RECIST criteria which only capture tumor volume change but miss out temporal information.…”
Section: Discussionsupporting
confidence: 87%
“…Tumor growth rate (TGR) provides quantitative assessment of change in tumor volume over time according to RECISTdefined sum of the longest diameters of the target lesions (SLD) from two computed tomography (CT) scans and time interval between them (17). Previous studies have showed that TGR was correlated with treatment response or clinical outcomes in patients with neuroendocrine carcinoma, renal cell carcinoma, or hepatocellular carcinoma treated with angiogenesis inhibitors or transarterial chemoembolization (18)(19)(20)(21)(22)(23). These findings suggested that TGR could serve as an early radiological biomarker to predict patient's survival outcomes and to tailor radiological follow-up strategies and patients' management.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of HPD was not exclusive to non-immunotherapeutic agents. Purcell et al found that pre-treatment TGR could predict treatment response in patients treated with TACE [35]. We evaluated the data of patients treated with TKI as the control group but did not observe that this group satisfied the criteria for HPD.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of fewer tumors, tumor size <5 cm, and a higher proportion of arterial enhanced tumors have been associated with a better treatment response rate [18]. On the contrary, hypovascular tumors and those located in segment I or IV have been associated with poorer treatment response [18, 19]. Several pre-TACE prediction models that were developed to estimate treatment response to TACE showed promising initial results [20-25].…”
Section: Introductionmentioning
confidence: 99%